Clinical evidence for association of neoadjuvant chemotherapy or chemoradiotherapy with efficacy and safety in patients with resectable esophageal carcinoma (NewEC study) - Zhou, Hai-Yu; Zheng, Shao-Peng; Li, An-Lin; Gao, Quan-Long; Ou, Qi-Yun; Chen, Yong-Jian; Wu, Shao-Tao; Lin, Da-Gui; Liu, Sheng-Bo; Huang, Lu-Yu; Li, Fa-Sheng; Zhu, Hong-Yuan; et al. (EClinicalMedicine, 2020)
The efficacy and safety of neoadjuvant treatment over surgery alone and that of neoadjuvant chemoradiotherapy (NCRT) over neoadjuvant chemotherapy (NCT) in resectable esophageal carcinoma remains inconclusive. This study (NewEC) used global data to comprehensively evaluate these comparisons and to provide a preferable strategy for patient subsets. This study included a meta-analysis of randomized controlled trials (RCTs) identified from inception to May 2019 from PubMed, EMBASE, the Cochrane Central Register of Controlled Trials, ClinicalTrials.gov, and congresses and a registry-based cohort study with patients from Massachusetts General Hospital (Massachusetts, USA) and Guangdong Provincial People's Hospital (Guangzhou, China) recruited from November 2000 and June 2017, to cross-validate the comparisons among NCRT versus NCT versus surgery. The GRADE approach was used to assessed quality of evidence in meta-analysis. Neural network machine learning propensity score–matched analysis was used to account for confounding by patient-level characteristics in the cohort study. The primary endpoint was overall survival (OS). The study was registered with PROSPERO CRD42017072242 and ClinicalTrials.gov NCT04027543. Of 22,070 studies assessed, there were 38 (n = 6,993 patients) eligible RCTs. Additionally, 423 out of 467 screened patients were included in the cohort study. The results from trials showed that NCT had a better OS than surgery alone (hazard ratio [HR] 0·88, 95% confidence interval [CI] 0·79–0·98; high quality) and was only favorable for adenocarcinoma (HR 0·83, 95% CI 0·72–0·96; moderate quality). High-quality evidence showed a significantly better OS for NCRT than surgery alone (HR 0·74, 95% CI 0·66–0·82) for both adenocarcinoma (HR 0·73, 95% CI 0·62–0·86) and squamous cell carcinoma (SCC) (HR 0·73, 95% CI 0·65–0·83). The OS benefit of NCRT over NCT was seen in the pairwise (HR 0·78, 95% CI 0·62–0·99; high quality) and network (HR 0·82, 95% CI 0·72–0·93; high quality) meta-analyses, with similar results before (HR 0·60, 95% CI 0·40–0·91) and after (HR 0·44, 95% CI 0·25–0·77) matching in the cohort study, leading to a significantly increased 5-year OS rate in both adenocarcinoma and SCC before and after matching. The increased benefits from NCT or NCRT were not associated with the risk of 30-day or in-hospital mortality. NewEC Study provided high-quality evidence supporting the survival benefits of NCRT or NCT over surgery alone, with NCRT presenting the greatest benefit for resectable esophageal carcinoma. National Science and Technology Major Project, the National Natural Science Foundation of China, the Natural Science Foundation of Guangdong Province, the Guangzhou Science and Technology Major Program, the Medical artificial intelligence project of Sun Yat-Sen Memorial Hospital, the Guangdong Science and Technology Department, the Guangdong Province Medical Scientific Research Foundation, and Guangdong Provincial People's Hospital Intermural Program.